Food and physical literacy: Exploring an obesity prevention approach using formative research. (August 2019) - Gibson, Isla; Whitelaw, Sandy; Topping, Christopher; Kopela, Joanna
Objective: The objective of this research was to explore how accessible the concept of food and physical literacy is for health and well-being professionals, and assess its potential effect on service delivery. Design: Formative research and 'concept testing' with potential deliverers of food and physical literacy. Setting: Dumfries and Galloway, a rural region in South West Scotland, UK. Method: The research was undertaken after four workshops hosted by National Health Service (NHS) public health specialists, aiming to introduce and discuss the concept. An immediate post-event focus group and a short qualitative questionnaire were used to assess professionals' initial perspectives on the concept, whether they thought the concept was applicable to their work, and what they might require by way of support if the concept was to be taken forward. Results: The findings illustrated the extent to which professionals feel that food and physical literacy is necessary, barriers to its implementation and ideal components for advancing work within this field. Conclusion: The concept of food and physical literacy has a sufficiently high level of resonance (proof of the concept) among informants to provide a foundation on which further work on its operationalisation can be based. The use of formative research and concept testing with potential service deliverers was able to identify areas to be considered during developmental stages, increasing the likelihood that the end result will be accepted by the professionals expected to utilise it. Thus, the benefits of an inclusive approach to service development were also highlighted.